Discursos de Benito Mussolini: permanências e mudanças (1919-1922) - Caron, Giuseppe Rafael (2015)
This research, under the guidance of Prof. Dr. Antonio Pedro Tota, has as theme the ideology modification of Italian fascism from 1919 to 1922. The objective is to observe through Benito Mussolini's speeches the transformation of fascism before the seizure of power through of March on Rome. This work respond the following questions: Which led the Italian fascism to change in that short period of time? and What was fascism movement? As methodology was analyzed the speeches given by Duce in the years before the fascist government. The two of the leading historians of fascism, Renzo de Felice and Emilio Gentile together with Frances Speech analysis provided the theoretical basis for this research. As a result, we point out the need of fascism in negotiating with your audience, adapting to their realities, in addition, we can observe the increasing approximation of fascism with Italian culture